2019
DOI: 10.1103/physrevd.99.064004
|View full text |Cite
|
Sign up to set email alerts
|

Stable singularity-free cosmological solutions in nonprojectable Hořava-Lifshitz gravity

Abstract: We find stable singularity-free cosmological solutions in non-flat Friedmann-Lemaître-Robertson-Walker (FLRW) spacetime in the context of Hořava-Lifshitz (HL) theory. Although we encounter the negative squared effective masses of the scalar perturbations in the original HL theory, the behaviors can be remedied by relaxing the projectability condition. In our analysis, the effects from the background dynamics are taken into account as well as the sign of the coefficients in the quadratic action for perturbation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 148 publications
(164 reference statements)
1
6
0
Order By: Relevance
“…In low energy regime (λ → ∞), the evolution equation (31) of the TT tensor mode reduces to the standard one in general relativity as expected, i.e.,…”
Section: Equations Of Motionsupporting
confidence: 59%
See 3 more Smart Citations
“…In low energy regime (λ → ∞), the evolution equation (31) of the TT tensor mode reduces to the standard one in general relativity as expected, i.e.,…”
Section: Equations Of Motionsupporting
confidence: 59%
“…b) If γ = 1 4 ± 2 3 , then K 1 = 48 and K 2 = 0. Now, the asymptotic behavior of the evolution equation (31) reduces tö…”
Section: Solution IImentioning
confidence: 99%
See 2 more Smart Citations
“…In [9] the authors found that HL cosmology provide an alternative to inflation and that the universe can be singularity-free, for reviews of HL cosmology we refer the reader to [10,11]. Very few exact solutions exists in HL cosmology with or without any matter source [12][13][14][15][16], however, according to our knowledge the are not known analytical solutions in HL cosmology when a minimally scalar field contributes to the total evolution of the universe.…”
Section: Introductionmentioning
confidence: 99%